Effect of Brisk-Walk on Heart Sounds and Blood Pressure in Young Adults - Noorzaid Bin Muhamad; Ahmad Muhammad Bin Mohd Rosli; Dalili Auni Binti Muhammad Afandie; Muhammad Ihsan Syahidi Bin Abdul Latif; Nor Aqilah Binti Zaibudin; Nurul Alya Diana Binti Mohd Jusof; Siti Khadijah Binti Mohd Fuad; Syarifah Nor Amani Binti Sayed Azman; Nur Maisarah Binti Noorzaid; Yusuf Imran Noorzaid (Sumatera Medical Journal, 2026)
Background: Despite the potential significance of heart sounds in medical diagnoses, their integration into routine clinical assessment remains limited.  Objective: This study aims to learn the effect of brisk walking on heart sound, focusing on intervals between S1 and S2, and S2 and S1, and blood pressure in healthy young adults. Methods: A convenience sampling method was used. Eight young adult subjects were asked to complete a brisk 30-minute walk on a treadmill. Heart sounds of each subject were recorded by using an electronic stethoscope, and a blood pressure monitor was used to record systolic and diastolic blood pressure before and after the 30-minute walk. The same activity was repeated two weeks after the initial study. Results: A varying degree of change in the S1-S2 interval and S2-S1 interval was found. Males exhibit an increase in SBP post-walk compared to the decrease observed in females. However, the diastolic blood pressure in both genders showed a reduction after walking, and it is consistent with the expected cardiovascular response to exercise. Conclusion: There were significant changes in S1-S2, S2-S1 interval, systolic and diastolic blood pressure after brisk walking among the subjects.